Normoxic induction of HIF‐1α by adenosine‐A2BR signaling in epicardial stromal cells formed after myocardial infarction. Issue 5 (29th April 2021) - Hesse, Julia; Groterath, Wiebke; Owenier, Christoph; Steinhausen, Julia; Ding, Zhaoping; Steckel, Bodo; Czekelius, Constantin; Alter, Christina; Marzoq, Aseel; Schrader, Jürgen
Abstract: Myocardial infarction (MI) activates the epicardium to form epicardial stromal cells (EpiSC) that reside in the epicardial hypoxic microenvironment. Paracrine factors secreted by EpiSC were shown to modulate the injury response of the post‐MI heart and improve cardiac function. We have previously reported that the expression of the angiogenic cytokines vascular endothelial growth factor A (VEGFA) and IL‐6 is strongly upregulated in EpiSC by adenosine acting via the A2B receptor (A2B R). Since tissue hypoxia is well known to be a potent stimulus for the generation of extracellular adenosine, the present study explored the crosstalk of A2B R activation and hypoxia‐hypoxia‐inducible factor 1 alpha (HIF‐1α) signaling in cultured EpiSC, isolated from rat hearts 5 days after MI. We found substantial nuclear accumulation of HIF‐1α after A2B R activation even in the absence of hypoxia. This normoxic HIF‐1α induction was PKC‐dependent and involved upregulation of HIF‐1α mRNA expression. While the influence of hypoxia on adenosine generation and A2B R signaling was only minor, hypoxia and A2B R activation cumulatively increased VEGFA expression. Normoxic A2B R activation triggered an HIF‐1α‐associated cell‐protective metabolic switch and reduced oxygen consumption. HIF‐1α targets and negative regulators PHD2 and PHD3 were only weakly induced by A2B R signaling, which may result in a sustained HIF‐1α activity. The A2B R‐mediated normoxic HIF‐1α induction was also observed in cardiac fibroblasts from healthy mouse hearts, suggesting that this mechanism is also functional in other A2B R‐expressing cell types. Altogether, we identified A2B R‐mediated HIF‐1α induction as novel aspect in the HIF‐1α‐adenosine crosstalk, which modulates EpiSC activity and can amplify HIF‐1α‐mediated cardioprotection.